Гибридные энергонакопители на основе аккумуляторов и суперконденсаторов для контактной микросварки - Bondarenko, Yu. V.; Safronov, P. S.; Bondarenko, O. F.; Sydorets, V. M.; Rogozina, T. S. (PE "Politekhperiodika", Book and Journal Publishers, 2014)
Micro resistance welding is an effective way to reliably join small-scale parts. It is widely used in electronics and instrument-making. The important particularities of micro resistance welding are pulse character of energy consumption, non-linear load and special form of current pulses. So, these particularities of welding process cause negative influence on the mains. One of the known ways to avoid it is to use autonomous power supplies for micro resistance welding machines. The important task for building autonomous power supplies is to choose effective energy storages, which have high capacity and small internal resistance, and which are capable to be charged and deliver energy to load very quickly. The solution of this task is seen in using hybrid energy storages, which include accumulators and ultracapacitors. The accumulators are able to provide high energy capacitance and the ultracapacitors are able to provide fast energy delivery. The possibility of application of hybrid energy storages, based on accumulator batteries and ultracapacitors, in micro resistance welding machines is confirmed with computer simulation. Two variants of hybrid energy storages are proposed. These hybrid energy storages have high power and dynamic characteristics, which are sufficient to generate current pulses for welding according to necessary settings.